Cardiac rehabilitation in German speaking countries of Europe: evidence-based guidelines from Germany, Austria and Switzerland LLKardReha-DACH : Part 1 : Review - Rauch, Bernhard; Salzwedel, Annett; Bjarnason-Wehrens, Birna; Albus, Christian; Meng, Karin; Schmid, Jean-Paul; Benzer, Werner; Hackbusch, Matthes; Jensen, Katrin; Schwaab, Bernhard; Altenberger, Johann; Benjamin, Nicola; et al. (Journal of Clinical Medicine, 2021)
Background: Although cardiovascular rehabilitation (CR) is well accepted in general, CR-attendance and delivery still considerably vary between the European countries. Moreover, clinical and prognostic effects of CR are not well established for a variety of cardiovascular diseases. Methods: The guidelines address all aspects of CR including indications, contents and delivery. By processing the guidelines, every step was externally supervised and moderated by independent members of the “Association of the Scientific Medical Societies in Germany” (AWMF). Four meta-analyses were performed to evaluate the prognostic effect of CR after acute coronary syndrome (ACS), after coronary bypass grafting (CABG), in patients with severe chronic systolic heart failure (HFrEF), and to define the effect of psychological interventions during CR. All other indications for CR-delivery were based on a predefined semi-structured literature search and recommendations were established by a formal consenting process including all medical societies involved in guideline generation. Results: Multidisciplinary CR is associated with a significant reduction in all-cause mortality in patients after ACS and after CABG, whereas HFrEF-patients (left ventricular ejection fraction <40%) especially benefit in terms of exercise capacity and health-related quality of life. Patients with other cardiovascular diseases also benefit from CR-participation, but the scientific evidence is less clear. There is increasing evidence that the beneficial effect of CR strongly depends on “treatment intensity” including medical supervision, treatment of cardiovascular risk factors, information and education, and a minimum of individually adapted exercise volume. Additional psychologic interventions should be performed on the basis of individual needs. Conclusions: These guidelines reinforce the substantial benefit of CR in specific clinical indications, but also describe remaining deficits in CR-delivery in clinical practice as well as in CR-science with respect to methodology and presentation.
Gesehen am 21.09.2021